Polyamide material containing lithium ion sieve and separation membrane and preparation method thereof

By developing polyamide materials and separation membranes containing lithium ion sieves in a salt lake, using the interfacial polymerization technology between the polyamide skeleton and lithium ion sieve, the problem of low separation efficiency between lithium ions and magnesium ions is solved, and efficient separation of magnesium and lithium ions is achieved and stable water flux, suitable for the purification of lithium resources in salt lakes.

CN119320492AActive Publication Date: 2025-01-17CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202310878059.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-17
Publication Date
2025-01-17
Estimated Expiration
2043-07-17

AI Technical Summary

Technical Problem

The prior art has low separation efficiency between lithium ions and magnesium ions in salt lakes, and it is difficult to effectively improve the separation efficiency of magnesium lithium, especially in the case of high magnesium lithium ratio.

Method used

Develop a polyamide material and separation membrane containing lithium ion sieve. The polyamide skeleton and the lithium ion sieve structural unit are polymerized through the interface of the polyamide skeleton to form a separation membrane with high separation coefficient and water flux. The lithium ion sieve is modified by aminosilane. and bonded to the polyamide material to ensure its stable load.

Benefits of technology

It achieves a high magnesium lithium separation efficiency and water flux. The lithium-ion sieve is not easy to fall off during multiple uses, and the separation membrane has stable performance and is suitable for practical applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004344099890000021
    Figure BDA0004344099890000021
  • Figure BDA0004344099890000031
    Figure BDA0004344099890000031
  • Figure BDA0004344099890000061
    Figure BDA0004344099890000061
Patent Text Reader

Abstract

The invention relates to the field of separation and extraction, and discloses a polyamide material containing a lithium ion sieve, a separation membrane and preparation methods of the polyamide material and the separation membrane. The preparation method of the polyamide material containing the lithium ion sieve comprises the following steps: carrying out interfacial polymerization on a dispersion liquid containing polyamine and a solution containing polyacyl chloride to form the polyamide material, wherein the dispersion liquid containing the polyamine also contains an amino silane modified lithium ion sieve. When the membrane containing the polyamide material is applied to magnesium-lithium separation, a high magnesium-lithium separation coefficient can be obtained, and the membrane is more stable in performance and more suitable for actual use.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of separation and extraction, and in particular to a polyamide material and a separation membrane containing a lithium ion sieve and a preparation method thereof. Background Art

[0002] Most of my country's lithium resources are stored in salt lake brine. In addition to lithium ions, salt lake water also contains a large amount of magnesium ions and sodium ions. According to the diagonal rule, magnesium ions and lithium ions have similar radii and properties, and it is difficult to separate the two. The high magnesium-to-lithium ratio is a major feature of my country's salt lakes, so purifying lithium from salt lakes is a major challenge.

[0003] The separation efficiency of currently commercialized membranes for magnesium ions and lithium ions is very low. The improvement in magnesium-lithium separation efficiency is due to the high rejection rate of divalent magnesium ions and the high permeability to monovalent lithium ions. The existing technology usually improves the magnesium-lithium separation efficiency by increasing the rejection rate of magnesium ions. Therefore, it is urgent to develop a technology that can improve the permeability of monovalent lithium ions while improving the rejection rate of divalent magnesium ions, so as to achieve magnesium-lithium separation with higher separation efficiency. Summary of the invention

[0004] The purpose of the present invention is to overcome the problem of low magnesium-lithium separation efficiency in the prior art, and to provide a polyamide material and a separation membrane containing a lithium ion sieve and a method for preparing the same, wherein the separation membrane can achieve magnesium-lithium separation with a higher separation coefficient.

[0005] In order to achieve the above object, the first aspect of the present invention provides a polyamide material containing a lithium ion sieve, the material comprising a polyamide skeleton and a structural unit as shown in formula (I) connected to the polyamide skeleton,

[0006]

[0007] In formula (I), R 1 R is selected from H, C1-C6 alkyl and C1-C6 amine; 2 Selected from H, -OM 3 and C1-C6 alkyl, M 1 、M 2 and M 3 Each is independently a lithium ion sieve.

[0008] A second aspect of the present invention provides a separation membrane, which comprises a separation layer, wherein the separation layer comprises the polyamide material containing the lithium ion sieve as described in the first aspect.

[0009] The third aspect of the present invention provides a method for preparing a polyamide material containing a lithium ion sieve, the method comprising: using a dispersion containing a polyamine and a solution containing a polyacyl chloride to form the polyamide material through interfacial polymerization;

[0010] The polyamine-containing dispersion also contains aminosilane-modified lithium ion sieve.

[0011] The fourth aspect of the present invention provides a method for preparing a separation membrane, which method includes the method for preparing the polyamide material containing the lithium ion sieve described in the third aspect.

[0012] The fifth aspect of the present invention provides a separation membrane prepared by the method described in the fourth aspect.

[0013] The polyamide material provided by the present invention, when applied to magnesium-lithium separation, can obtain a higher separation coefficient and water flux, and the lithium ion sieve can be stably loaded on the polyamide material. The separation membrane containing the polyamide material provided by the present invention can achieve magnesium-lithium separation with a higher separation coefficient, with a higher lithium permeability and a higher water flux. In addition, after the lithium ion sieve is modified by aminosilane, it is loaded on the separation membrane by bonding, so that the structure is more stable, and the lithium ion sieve will not fall off after repeated use, and the performance is more stable, which is more suitable for practical use. DETAILED DESCRIPTION

[0014] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0015] In a first aspect, the present invention provides a polyamide material containing a lithium ion sieve, the material comprising a polyamide skeleton and a structural unit as shown in formula (I) connected to the polyamide skeleton,

[0016]

[0017] In formula (I), R 1 R is selected from H, C1-C6 alkyl and C1-C6 amine; 2 Selected from H, -OM 3 and C1-C6 alkyl, M 1 、M 2 and M 3 Each is independently a lithium ion sieve.

[0018] Among them, M 1 、M2 and M 3 can be the same or different. In a preferred embodiment, M 1 、M 2 and M 3 same.

[0019] The inventors of the present invention have found in their research that when the polyamide material is used for magnesium-lithium separation, a higher magnesium-lithium separation coefficient and a higher water flux can be obtained. In particular, the lithium ion sieve is bonded to the polyamide material by bonding, so that the load of the lithium ion sieve on the polyamide material can be more stable. The membrane containing the polyamide material will not cause the lithium ion sieve to fall off after repeated use, and has stable performance and is more suitable for practical use.

[0020] According to the present invention, preferably, relative to the total mass of the polyamide material, the mass content of the lithium ion sieve is 0.05-2.2wt%, more preferably 0.7-1.5wt% (for example, it can be 0.7wt%, 0.8wt%, 0.9wt%, 1wt%, 1.1wt%, 1.2wt%, 1.3wt%, 1.4wt%, 1.5wt% and the range formed by any two of the above values ​​and the value within the range). The lithium ion sieve content in the polyamide material can be characterized by X-ray photoelectron spectroscopy.

[0021] According to the present invention, preferably, the lithium ion sieve is selected from at least one of aluminum hydrotalcite bimetallic oxide lithium ion sieve, manganese oxide lithium ion sieve and titanium oxide lithium ion sieve, more preferably Li 1.33 Mn 1.67 O 4 , Li 2 TiO 3 and Li 4 Mn 5 O 12 At least one of .

[0022] Preferably, R 1 is propyl, R 2 Yes-OM 3 base.

[0023] Preferably, R 1 is propyl, R 2 It's methyl.

[0024] Preferably, R 1 is ethyl n-propylamino, R 2 It's methyl.

[0025] Preferably, R 1 is ethyl n-propylamino, R 2 Yes-OM 3 base.

[0026] In the above case, it can be further ensured that the polyamide material has a higher separation coefficient and water flux when used for magnesium-lithium separation.

[0027] A second aspect of the present invention provides a separation membrane, which includes a separation layer, wherein the separation layer includes the polyamide material containing the lithium ion sieve described in the first aspect.

[0028] As described above, when the separation membrane includes the polyamide material described in the first aspect, it has a higher separation factor and water flux when applied to magnesium-lithium separation, and the membrane has good long-term stability.

[0029] According to a particularly preferred embodiment of the present invention, the material of the separation layer is the polyamide material described in the first aspect.

[0030] According to the present invention, preferably, the separation membrane comprises a bottom layer, a porous support layer and a separation layer in sequence.

[0031] According to the present invention, preferably, the porosity of the bottom layer is 35-60% (for example, it can be 35%, 40%, 45%, 50%, 55%, 60% and the range formed by any two of the above values ​​and the values ​​within the range).

[0032] Preferably, the thickness of the bottom layer is 30-150 μm, more preferably 50-120 μm (for example, it can be 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, 120 μm, and ranges formed by any two of the above values ​​and values ​​within the range).

[0033] Preferably, the thickness of the porous support layer is 10-100 μm, preferably 30-60 μm (for example, it can be 30 μm, 40 μm, 50 μm, 60 μm, and a range formed by any two of the above values ​​and a value within the range).

[0034] Preferably, the average pore size of the porous support layer is 15-30 nm (for example, it may be 15 nm, 18 nm, 20 nm, 23 nm, 25 nm, 28 nm, 30 nm, and a range formed by any two of the above values, and a value within the range).

[0035] According to the present invention, preferably, the material of the bottom layer is selected from polyester and / or polyethylene. The bottom layer can be a non-woven fabric comprising the above materials.

[0036] According to the present invention, preferably, the material of the porous support layer is selected from at least one of polyethersulfone, polysulfone, polyaromatic ether, polybenzimidazole, polyetherketone, polyetheretherketone, polyacrylonitrile, polyvinylidene fluoride and polyaryletherketone, and the weight-average molecular weight of the material of the porous support layer is 50-150kDa (for example, it can be 50kDa, 70kDa, 90kDa, 100kDa, 130kDa, 150kDa, and the range formed by any two of the above values ​​and the value within the range).

[0037] According to the present invention, preferably, the thickness of the separation layer is 80-110 nm (for example, it can be 80 nm, 90 nm, 100 nm, 110 nm, and a range formed by any two of the above values, and a value within the range).

[0038] According to the present invention, preferably, the average pore size of the separation layer is 0.2-0.3 nm.

[0039] In a third aspect, the present invention provides a method for preparing a polyamide material containing a lithium ion sieve, the method comprising: using a dispersion containing a polyamine and a solution containing a polyacyl chloride to form the polyamide material through interfacial polymerization;

[0040] The polyamine-containing dispersion also contains aminosilane-modified lithium ion sieve.

[0041] The inventors of the present invention have found in the research that in the process of the above-mentioned interfacial polymerization, polyamines can form a polyamide skeleton with polyacyl chlorides. At the same time, in the presence of amino and carbonyl groups, aminosilane-modified lithium ion sieves can also react with other carbonyl groups in polyacyl chlorides that do not react with polyamines to form amide bonds, thereby forming a structural unit having the above-mentioned formula (I), that is, part of the carbonyl groups from polyacyl chlorides in the polyamide are used to form repeating units of polyamide with polyacyl chlorides, and part of the carbonyl groups are bonded to amino-modified lithium ion sieves. In this way, the lithium ion sieve is bonded to the polyamide skeleton through aminosilane, so that not only the prepared polyamide material can have a higher separation coefficient and a higher water flux when applied to magnesium-lithium separation, but also the lithium ion sieve is stably loaded on the polyamide skeleton, and the material has long-term stability.

[0042] According to the present invention, preferably, the interfacial polymerization is performed on a substrate.

[0043] According to the present invention, preferably, the interfacial polymerization method comprises: contacting the surface of the substrate with a dispersion containing polyamine and a solution containing polyacyl chloride in sequence.

[0044] According to the present invention, preferably, the polyamine is selected from at least one of polyethyleneimine, triethylenetetramine, tetraethylenepentamine, diethylenetriamine, polyethylenepolyamine, piperazine, m-phenylenediamine and p-phenylenediamine, more preferably polyethyleneimine and / or piperazine.

[0045] Wherein, when the polyamine is a polymer, the weight-average molecular weight of the polymer can be 10,000-120,000 g / mol (for example, it can be 10,000 g / mol, 20,000 g / mol, 30,000 g / mol, 40,000 g / mol, 50,000 g / mol, 60,000 g / mol, 70,000 g / mol, 80,000 g / mol, 90,000 g / mol, 100,000 g / mol, 110,000 g / mol, 120,000 g / mol, and the range formed by any two of the above values ​​and the value within the range).

[0046] According to the present invention, preferably, the polyacyl chloride is selected from at least one of trimesoyl chloride, terephthaloyl chloride, isophthaloyl chloride and phthaloyl chloride, more preferably trimesoyl chloride and / or terephthaloyl chloride.

[0047] According to the present invention, preferably, in the dispersion containing polyamine, the mass concentration of the polyamine is 0.1-3wt%, preferably 0.5-2.5wt% (for example, it can be 0.5wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt% and the range formed by any two of the above values ​​and the value of the range).

[0048] According to the present invention, preferably, the aminosilane-modified lithium ion sieve has a structure as shown in formula (II):

[0049]

[0050] In formula (I), R 1 R is selected from H, C1-C6 alkyl and C1-C6 amine; 2 Selected from H, -OM 3 and C1-C6 alkyl, M 1 、M 2 and M 3 Each is independently a lithium ion sieve.

[0051] According to the present invention, preferably, the preparation method of the aminosilane-modified lithium ion sieve comprises: mixing the lithium ion sieve and aminosilane in a solution state, and performing a modification reaction under acidic conditions. By adopting this method, a structure as shown in formula (II) can be prepared. The lithium ion sieve powder can be first dispersed in water and further dispersed by ultrasound. Then, aminosilane is added to the dispersion.

[0052] According to the present invention, preferably, the mass ratio of lithium ion sieve to aminosilane is 1:(0.1-1.5).

[0053] Preferably, the mass concentration of the lithium ion sieve in the solution is 0.5-1.5 mg / ml (for example, it can be 0.5 mg / ml, 0.6 mg / ml, 0.7 mg / ml, 0.8 mg / ml, 0.9 mg / ml, 1 mg / ml, 1.1 mg / ml, 1.2 mg / ml, 1.3 mg / ml, 1.4 mg / ml, 1.5 mg / ml, and the range formed by any two of the above values ​​and the value within the range).

[0054] Preferably, the acidic condition has a pH of 1-3.

[0055] Preferably, the conditions of the modification reaction also include: a temperature of 70-90°C (for example, it can be 70°C, 75°C, 80°C, 85°C, 90°C, and a range formed by any two of the above values, and a value within the range), and a time of 5-8h (for example, it can be 5h, 6h, 7h, 8h, and a range formed by any two of the above values, and a value within the range).

[0056] Under the above conditions, it is possible to further ensure that the structure shown in formula (II) is obtained.

[0057] Preferably, the preparation method of the aminosilane-modified lithium ion sieve further comprises: centrifuging, first drying, ball milling and second drying the material obtained by the modification reaction in sequence. The temperature of the first drying can be 70-120°C, and the time can be 3-6 hours; the temperature of the second drying can be 80-120°C, and the time can be 3-6 hours. Under the conditions of the first drying and the second drying, the water content in the material can generally be less than 0.05wt%. Ball milling is used to disperse the material, which can generally be completed in 25-40 minutes.

[0058] According to the present invention, preferably, in the modification reaction, the lithium ion sieve is selected from at least one of aluminum hydrotalcite bimetallic oxide lithium ion sieve, manganese oxide lithium ion sieve and titanium oxide lithium ion sieve, more preferably Li 1.33 Mn 1.67 O 4 , Li 2 TiO 3 and Li 4 Mn 5 O 12 At least one of .

[0059] According to the present invention, preferably, in the modification reaction, the average particle size of the lithium ion sieve is 10-200 nm (for example, it can be 10 nm, 20 nm, 30 nm, 50 nm, 100 nm, 150 nm, 200 nm, and the range formed by any two of the above values ​​and the value within the range).

[0060] According to the present invention, preferably, in the modification reaction, the aminosilane is selected from the structure shown in any one of formula (a) to formula (f);

[0061]

[0062] When the above aminosilane is used, it can be ensured that the prepared polyamide material has higher lithium permeability and higher water flux when applied to magnesium-lithium separation, and has better long-term stability.

[0063] According to the present invention, preferably, in the dispersion containing polyamine, the mass concentration ratio of the aminosilane-modified lithium ion sieve to the polyamine is 1:(4-60) (for example, it can be 1:4, 1:6, 1:10, 1:15, 1:20, 1:25, 1:30, 1:35, 1:40, 1:45, 1:50, 1:55, 1:60 and the ratio range formed by any two of the above ratios and the value within the range), more preferably 1:(10-50).

[0064] According to the present invention, preferably, relative to 1m 2 The amount of aminosilane-modified lithium ion sieve is 5-500 mg (for example, 5 mg, 10 mg, 50 mg, 100 mg, 150 mg, 200 mg, 300 mg, 400 mg, 500 mg, and any range formed by any two of the above values ​​and values ​​within the range). It can be understood that the amount is generally greater than the amount that can react and thus exist on the separation layer.

[0065] According to the present invention, preferably, in the solution containing polyacid chloride, the concentration of polyacid chloride is 0.01-1wt%, preferably 0.05-0.5wt% (for example, it can be 0.05wt%, 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt% and the range formed by any two of the above values ​​and the value within the range).

[0066] The solvent in the solution containing polyacid chloride is not particularly limited, and can be, for example, Isopar E solution or Isopar G solution (the above are isoparaffin solvent oils).

[0067] According to the present invention, preferably, the ratio of the mass of the polyamine in the dispersion containing the polyamine to the mass of the polyacid chloride in the solution containing the polyacid chloride is (0.1-20):1, more preferably (0.5-10):1.

[0068] According to the present invention, preferably, the substrate is in contact with the dispersion containing polyamine for 5-100 seconds, preferably 10-60 seconds, and the contact temperature is 20-40° C., preferably 28-32° C. After contacting with the dispersion containing polyamine, the material can be taken out and the excess solution on the surface of the material can be removed with a rubber roller.

[0069] According to the present invention, preferably, the substrate is in contact with the solution containing polyacid chloride for 10-200 s, preferably 20-120 s, and the contact temperature is 20-40°C, preferably 28-32°C.

[0070] According to the present invention, preferably, after contacting with the dispersion containing polyamine and the solution containing polyacid chloride, the method further comprises: heat-treating the product after interfacial polymerization.

[0071] Preferably, the heat treatment conditions include: a temperature of 40-150°C, preferably 50-120°C; a heat treatment time of 0.5-10 minutes, preferably 1-5 minutes. The heat treatment can be carried out in a vacuum oven.

[0072] In a fourth aspect, the present invention provides a method for preparing a separation membrane, the method comprising the method for preparing a polyamide material containing a lithium ion sieve as described in the third aspect.

[0073] According to the present invention, preferably, the interfacial polymerization is carried out on a substrate comprising a porous supporting layer and a bottom layer.

[0074] According to the present invention, preferably, the conditions for the interfacial polymerization further include making the thickness of the separation layer 80-110 nm.

[0075] According to the present invention, preferably, the method also includes the step of preparing a porous supporting layer on the bottom layer, the step comprising: coating a solution containing a porous supporting layer material on the bottom layer (for example, coating can be performed using a scraper), and soaking the solution in water at 10-30°C for 10-60 minutes to form a porous supporting layer on the surface of the bottom layer; the conditions for preparing the porous supporting layer preferably include making the thickness of the porous supporting layer 10-100 μm, preferably 30-60 μm.

[0076] Preferably, in the solution containing the porous support layer material, the mass concentration of the porous support layer material is 10-20wt% (for example, it can be 10wt%, 11wt%, 12wt%, 13wt%, 14wt%, 15wt%, 16wt%, 17wt%, 18wt%, 19wt%, 20wt% and the range formed by any two of the above values ​​and the values ​​within the range).

[0077] The solvent in the solution containing the porous support layer material is not particularly limited, but preferably, the solvent in the solution containing the porous support layer material is at least one of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone and dimethyl sulfoxide.

[0078] According to the present invention, preferably, the thickness of the bottom layer is 30-150 μm, preferably 50-120 μm (for example, it can be 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, 120 μm, and the range formed by any two of the above values ​​and the value within the range).

[0079] According to the present invention, preferably, the material of the bottom layer is selected from polyester and / or polyethylene.

[0080] According to the present invention, preferably, the porosity of the bottom layer is 35-60% (for example, it can be 35%, 40%, 45%, 50%, 55%, 60% and the range formed by any two of the above values ​​and the values ​​within the range).

[0081] According to the present invention, preferably, the material of the porous support layer is selected from at least one of polyethersulfone, polysulfone, polyaromatic ether, polybenzimidazole, polyetherketone, polyetheretherketone, polyacrylonitrile, polyvinylidene fluoride and polyaryletherketone, and the weight average molecular weight of the material of the porous support layer is 50-150kDa.

[0082] The material of the porous supporting layer may be dissolved in a solvent, and the solution is then degassed at 22-28° C. for 1.5-3 h.

[0083] In a fifth aspect, the present invention provides a separation membrane prepared by the method described in the fourth aspect.

[0084] The present invention will be described in detail below through examples. In the following examples, the thickness of the porous support layer and the separation layer is determined by scanning electron microscopy. The thickness of the separation layer refers to the thickness of the membrane layer formed by interfacial polymerization, and does not include the influence of the particle size of the lithium ion sieve particles.

[0085] In the following examples, before interfacial polymerization, the average pore size of the porous support layer was measured by a pore size analyzer (model: PSDA-20, purchased from Nanjing Gaoqian) for the material containing the porous support and the bottom layer.

[0086] The average pore size of the separation layer was determined by using the PEG solute transfer method (see Journal of membrane science, 281 (2006), 307-315).

[0087] The content of the modified lithium ion sieve in the membrane (ie, the content of the modified lithium ion sieve in the separation layer in Table 1) is determined by the metal ion content measured by X-ray photoelectron spectroscopy (XPS).

[0088] In the following examples and comparative examples:

[0089] The material containing a porous support and a bottom layer used in Examples 1-7 is prepared by a phase inversion method on the bottom layer. The specific steps are as follows: a certain amount of polysulfone (weight average molecular weight of 80 kDa) is dissolved in N,N-dimethylformamide to prepare a polysulfone solution with a concentration of 18 wt%, and degassing at 25°C for 120 min; then, the polysulfone solution is coated on a polyester non-woven fabric (with a thickness of 75 μm) (with a porosity of 40%) using a scraper, and then the non-woven fabric is immersed in water at a temperature of 25°C for 60 min to phase-invert the polysulfone layer on the surface of the polyester non-woven fabric, and finally washed with water three times to obtain a material with a porous support and a bottom layer.

[0090] The material containing a porous support and a bottom layer used in Example 8, the porous support layer on the bottom layer is prepared by a phase inversion method, and the specific steps are as follows: a certain amount of polysulfone (weight average molecular weight of 100 kDa) is dissolved in N,N-dimethylformamide to prepare a polysulfone solution with a concentration of 20wt%, and degassing at 25°C for 120min; then, the polysulfone solution is coated on a polyester non-woven fabric (with a thickness of 100μm) (porosity of 30%) using a scraper, and then it is immersed in water at a temperature of 22°C for 50min, so that the polysulfone layer on the surface of the polyester non-woven fabric undergoes a phase inversion, and finally the material containing a porous support and a bottom layer is obtained after three water washes.

[0091] The material containing a porous support and a bottom layer used in Example 9 is prepared by a phase inversion method on the bottom layer. The specific steps are as follows: a certain amount of polysulfone (weight average molecular weight of 120 kDa) is dissolved in N,N-dimethylformamide to obtain a polysulfone solution with a concentration of 19 wt%, and degassing is carried out at 25°C for 120 min; then, the polysulfone solution is coated on a polyester non-woven fabric (with a thickness of 80 μm) (with a porosity of 60%) using a scraper, and then the non-woven fabric is immersed in water at a temperature of 27°C for 45 min to phase-invert the polysulfone layer on the surface of the polyester non-woven fabric, and finally washed with water three times to obtain a material containing a porous support and a bottom layer.

[0092] In the following examples and comparative examples:

[0093] (1) The water flux of the membrane is tested by the following method: the composite nanofiltration membrane is placed in a membrane pool, the water permeation of the nanofiltration membrane is measured under 0.6 MPA and a temperature of 25°C within a certain period of time, and the water flux is calculated by the following formula:

[0094] J = Q / (A·t), where J is the water flux, Q is the water permeation (L), and A is the effective membrane area of ​​the composite nanofiltration membrane (m 2 ), t is time (h);

[0095] (2) The salt rejection rate and magnesium-lithium separation coefficient of the composite nanofiltration membrane were tested by the following method: the composite nanofiltration membrane was placed in a membrane pool, the original aqueous solution was a mixture of 2000 ppm magnesium chloride and 100 ppm lithium chloride, and after pre-pressing at 0.2 MPa for 0.5 h, the permeate was obtained at a pressure of 0.6 MPa, the magnesium chloride and lithium chloride concentrations in the permeate were measured by ion chromatography, and the salt rejection rate was calculated by the following formula:

[0096] R = (Cp-Cf) / Cp×100%, where R is the desalination rate, Cp is the concentration of magnesium chloride or lithium chloride in the stock solution (measured by ion chromatography), and Cf is the concentration of magnesium chloride or lithium chloride in the permeate (measured by ion chromatography);

[0097] The lithium-magnesium separation coefficient is calculated by the following formula:

[0098]

[0099] Where S is the lithium-magnesium separation coefficient, C Li,p and C Li,f are the concentrations of lithium ions in the permeate and raw material solution (measured by ion chromatography); C Mg,p and C Mg,f are the concentrations of magnesium ions in the permeate and raw solution (measured by ion chromatography), respectively.

[0100] Preparation Example 1

[0101] Lithium ion powder Li 1.33 Mn 1.67 O 4 (20nm) is dispersed in water and ultrasonically dispersed for 10 minutes. Then, the aminosilane shown in formula (a) is added to the above dispersion to make its concentration 0.5mg / ml, the concentration of lithium ion sieve powder is 0.8mg / ml, the ratio of lithium ion sieve powder: formula (a) is 1:0.625 (mass ratio), and the pH of the reaction system is adjusted to 3 with dilute hydrochloric acid. React at a temperature of 80°C for 6h, centrifuge, and dry (temperature of 80°C, time of 3h) the obtained product. Then ball mill the above material for 30min and dry (temperature of 110°C, time of 3h) to a water content of less than 0.05wt%, to obtain aminosilane-modified lithium ion sieve A.

[0102]

[0103] Preparation Example 2

[0104] Lithium ion powder Li1.33 Mn 1.67 O 4 (20nm) is dispersed in water and ultrasonically dispersed for 10 minutes. Then, the aminosilane shown in formula (b) is added to the above dispersion to make its concentration 0.8mg / ml, the concentration of lithium ion sieve powder is 0.8mg / ml, the ratio of lithium ion sieve powder: formula (b) is 1:1 (mass ratio), and the pH of the reaction system is adjusted to 3 with dilute hydrochloric acid. React at a temperature of 70°C for 6h, centrifuge, and dry (temperature is 80°C, time is 3h) to obtain the product. Then ball mill the above material for 30min and dry (temperature is 110°C, time is 3h), and the water content is less than 0.05wt% to obtain aminosilane-modified lithium ion sieve B.

[0105]

[0106] Preparation Example 3

[0107] The same as Preparation Example 1, except that the aminosilane represented by formula (a) is replaced by the aminosilane represented by formula (e), to obtain an aminosilane-modified lithium ion sieve C.

[0108]

[0109] Preparation Example 4

[0110] Lithium ion powder Li 2 TiO 3 (100nm) is dispersed in water and ultrasonically dispersed for 10 minutes. Then, the aminosilane shown in formula (a) is added to the above dispersion to make its concentration 1.2mg / ml, and the concentration of lithium ion sieve powder is 0.8mg / ml, then the ratio of lithium ion sieve powder: shown in formula (a) is 1:1.5 (mass ratio), and the pH of the reaction system is adjusted to 2 with dilute hydrochloric acid. React at a temperature of 90°C for 6h, centrifuge, and dry (temperature is 80°C, time is 3h) the obtained product. Then ball mill the above material for 30min, and dry (temperature is 110°C, time is 3h), the water content is less than 0.05wt%, and the aminosilane-modified lithium ion sieve D is obtained.

[0111] Preparation Example 5

[0112] Lithium ion powder Li 1.33 Mn 1.67 O 4(200nm) was dispersed in water and ultrasonically dispersed for 10 minutes, and then the aminosilane shown in formula (a) was added to the above dispersion to make its concentration 2.2mg / ml, and the concentration of lithium ion sieve powder was 1.3mg / ml, then the ratio of lithium ion sieve powder: formula (a) was 1:1.7 (mass ratio), and the pH of the reaction system was adjusted to 1 with dilute hydrochloric acid. The reaction was carried out at a temperature of 70°C for 5h, centrifuged, and dried (temperature of 80°C, time of 3h) to obtain the product. Then the above material was ball milled for 30min and dried (temperature of 110°C, time of 3h), and the water content was less than 0.05wt%, to obtain aminosilane-modified lithium ion sieve E.

[0113] Example 1

[0114] A material containing a porous support layer and a bottom layer (area 400cm 2 ), contacted with a dispersion of 0.8wt% polyethyleneimine (weight average molecular weight 100,000 g / mol) at 30°C for about 30 seconds, wherein the polyethyleneimine aqueous solution contains 0.03wt% aminosilane-modified lithium ion sieve A, and the material soaked in the polyethyleneimine aqueous solution is freed of excess solution with a rubber roller. The volume of the polyethyleneimine dispersion is such that, relative to 1m 2 The amount of the aminosilane-modified lithium ion sieve used is 25 mg.

[0115] Then, the material was contacted with an Isopar E solution containing 0.1 wt % of trimesoyl chloride (the volume of the solution was the same as the volume of the dispersion containing polyethyleneimine) at 30° C. for 30 seconds; then, the material was placed in a vacuum oven at 70° C. for 5 minutes to obtain a membrane M1.

[0116] According to the reaction mechanism, in this embodiment, in the structural unit shown in (I) in the separation layer, R 1 is propyl, R 2 It is -O-lithium ion sieve group.

[0117] After the obtained composite membrane M1 was immersed in water for 24 hours, the water flux and the desalination rate of magnesium chloride and lithium chloride were measured. The results are shown in Table 1.

[0118] Example 2

[0119] The same as Example 1, except that the polyethyleneimine dispersion contains 0.08 wt % of the modified lithium ion sieve. Membrane M2 was prepared.

[0120] Example 3

[0121] The same as Example 1, except that the concentration of the modified lithium ion sieve in the polyethyleneimine dispersion was 0.2 wt %. Membrane M3 was prepared.

[0122] Example 4

[0123] The same as Example 1, except that the modified lithium ion sieve B of Preparation Example 2 was used. Membrane M4 was prepared. According to the reaction mechanism, it can be determined that in this embodiment, in the structural unit shown in (I) of the polyamide material, R 1 is propyl, R 2 It is -O-lithium ion sieve group.

[0124] Example 5

[0125] The same as Example 1, except that the modified lithium ion sieve C of Preparation Example 3 was used. Membrane M5 was prepared. According to the reaction mechanism, it can be determined that in this embodiment, in the structural unit shown in (I) of the separation layer, R 1 is ethyl n-propylamino, R 2 It is -O-lithium ion sieve group.

[0126] Example 6

[0127] The same as Example 1, except that the modified lithium ion sieve D of Preparation Example 4 was used. Membrane M6 was prepared. According to the reaction mechanism, it can be determined that in this embodiment, in the structural unit shown in (I) of the separation layer, R 1 is propyl, R 2 It is -O-lithium ion sieve group.

[0128] Example 7

[0129] The same as Example 1, except that the modified lithium ion sieve E of Preparation Example 5 was used. A membrane M was prepared. According to the reaction mechanism, it can be determined that in this embodiment, in the structural unit shown in (I) of the separation layer, R 1 is propyl, R 2 It is -O-lithium ion sieve group.

[0130] Example 8

[0131] Using materials with porous support and bottom layer (area 400cm 2 ), contacted with a dispersion of piperazine at a concentration of 1.5 wt% at 32°C for about 45 seconds, wherein the piperazine dispersion contains 0.03 wt% of aminosilane-modified lithium ion sieve A, and the material soaked in the polyethyleneimine dispersion was freed of excess solution with a rubber roller. The volume of the polyethyleneimine dispersion was such that, relative to 1 m 2 The amount of the aminosilane-modified lithium ion sieve used is 25 mg.

[0132] The material was then contacted with an Isopar E solution containing 0.15 wt% of terephthaloyl chloride (the same volume as the dispersion containing piperazine) at 32°C for 45 seconds; the material was then placed in a vacuum oven at 80°C for 4 minutes to obtain film M8.

[0133] Example 9

[0134] Using materials with porous support and bottom layer (area 400cm 2 ), contacted with a dispersion of piperazine at a concentration of 1.2 wt% at 28°C for about 60 seconds, wherein the piperazine dispersion contains 0.03 wt% of aminosilane-modified lithium ion sieve A, and the material soaked with the polyethyleneimine aqueous solution was freed of excess solution with a rubber roller. The volume of the polyethyleneimine dispersion was such that, relative to 1 m 2 The amount of the aminosilane-modified lithium ion sieve used is 25 mg.

[0135] The material was then contacted with an Isopar E solution containing 0.4 wt% of terephthaloyl chloride (the same volume as the dispersion containing piperazine) at 28°C for 60 seconds; the material was then placed in a vacuum oven at 90°C for 3.5 minutes to obtain film M9.

[0136] Comparative Example 1

[0137] The membrane was prepared according to the method of Example 1, except that the polyethyleneimine dispersion did not contain the aminosilane-modified lithium ion sieve A. The membrane N1 was obtained. After the obtained composite membrane N1 was immersed in water for 24 hours, the water flux and the salt rejection rate of magnesium chloride and lithium chloride were measured. The results are shown in Table 1.

[0138] Comparative Example 2

[0139] The membrane was prepared according to the method of Example 1, except that the concentration of 0.03 wt% of aminosilane-modified lithium ion sieve A in the polyethyleneimine dispersion was replaced by 0.03 wt% of lithium ion sieve Li 1.33 Mn 1.67 O 4 (20 nm). Film N2 was obtained.

[0140] After the obtained membrane N2 was immersed in water for 24 hours, the water flux and the desalination rate of magnesium chloride and lithium chloride were measured. The results are shown in Table 1.

[0141] The volume of the polyamine dispersion in Example 2-7 and Comparative Example 1-2 is consistent with that in Example 1; the volume of the solution containing polyacid chloride in Example 2-7 and Comparative Example 1-2 is consistent with that in Example 1.

[0142] Table 1

[0143]

[0144] In Table 1, the content of the modified lithium ion sieve in the separation layer is the mass content of the lithium ion sieve relative to the total mass of the polyamide material.

[0145] The thickness of the porous support layer, the thickness of the separation layer, the average pore size of the porous support layer, and the average pore size of the separation layer of the membranes obtained in the above embodiments and preparation examples are shown in Table 2.

[0146] Table 2

[0147]

[0148] The separation layer in the membrane of Example 1-9 contains a modified lithium ion sieve, and compared with the membrane of Comparative Example 1, it has a higher magnesium chloride rejection rate and water flux, a higher lithium chloride permeability, and a high magnesium-lithium selectivity coefficient.

[0149] Compared with the membrane prepared by directly adding the lithium ion sieve into the aqueous phase in Comparative Example 2, the separation layer of the membranes of Examples 1-9 is thinner and has no defects (from the larger MgCl 2 The desalination rate can be seen), and the water flux is large, the retention rate of magnesium chloride is higher. And the long-term cycle stability is good (after one week of operation, it was found that the above parameters did not change significantly, but after one week of operation of the membrane of comparative example 2, MgCl 2 The desalination rate decreased by about 2%). The membranes prepared in Examples 1-9 were characterized by XPS (X-ray photoelectron spectroscopy). After one week of operation, the loading amount of the modified lithium ion sieve changed within the range of ±0.2wt%, and it can be basically considered that there was no shedding, indicating that the membrane provided by the present invention has a strong stability of the lithium ion sieve in the separation layer and is more suitable for practical use. For the membrane prepared in Comparative Example 2, after one week of operation, XPS characterization showed that the loading amount of the lithium ion sieve changed within the range of 3.8-7.2wt%. This indicates that after the amino-modified lithium ion sieve is introduced into the membrane through bonding, it has a good synergistic effect with the separation layer.

[0150] In addition, the amino-modified lithium ion sieve increases the compatibility of the aqueous phase and also reduces the diffusion rate of the aqueous phase monomer to the organic phase. The prepared membrane has a thinner separation layer and a suitable cross-linking density, so it also has a higher interception rate when the water flux is large. It can be found from Examples 1, 4 and 5 that the use of aminosilane with less steric hindrance increases the thickness of the separation layer under the same operating conditions, reduces the water flux of the membrane, and reduces the permeability of lithium chloride. It can be seen that the membrane prepared by the method of the present invention has a higher water flux and a suitable pore size, has a higher interception for magnesium chloride, and has a higher permeability for lithium chloride.

[0151] According to the reaction mechanism, when aminosilane and aminosilane are mixed and reacted under acidic conditions, the alkoxy group on the aminosilane can be hydrolyzed to form a Si-OH structure, and then will form a Si-O-lithium ion sieve structure in formula (II) with the modified lithium ion sieve. Therefore, when aminosilane and aminosilane are mixed and reacted under acidic conditions, a structure shown in formula (II) will be obtained.

[0152] Regarding the membranes prepared in Examples 1-9. During the interfacial polymerization process, when the polyamine attached to the material containing the porous support and the bottom layer contacts the carbonyl group of the polyacyl chloride, a reaction can occur to form a polyamide skeleton; on the other hand, the amino-modified ion sieve in the polyamine solution reacts with other carbonyl groups in the polyacyl chloride that have not reacted with the polyamine to form an amide bond, and together form a separation layer structural unit shown in formula (I), that is, other carbonyl groups in the structural unit from the polyacyl chloride in the polyamide and the amino-modified lithium ion sieve form a structure shown in formula (I). In this way, the lithium ion sieve is chemically bonded to the polyamide material and the separation layer to form a self-polymerized microporous thin layer composite nanofiltration membrane. Thanks to the lithium ion sieve in the separation layer and the pore structure matching the lithium ions, the prepared membrane has a good permeability to lithium ions. In addition, the modified lithium ion sieve added to the aqueous phase should also inhibit the diffusion rate of the polyamine during interfacial polymerization, so that the self-limitation of the interfacial polymerization reaction occurs earlier, and an ultra-thin separation layer is obtained, which greatly increases the permeability.

[0153] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A polyamide material containing a lithium ion sieve, characterized in that: The material comprises a polyamide skeleton and a structural unit as shown in formula (I) connected to the polyamide skeleton. In formula (I), R1 is selected from H, C1-C6 alkyl and C1-C6 amine; R2 is selected from H, -O-M3 and C1-C6 alkyl, and M1, M2 and M3 are each independently a lithium ion sieve.

2. The polyamide material according to claim 1, wherein Relative to the total mass of the polyamide material, the mass content of the lithium ion sieve is 0.05-2.2wt%, preferably 0.7-1.5wt%; And / or, the lithium ion sieve is selected from at least one of aluminum hydrotalcite bimetallic oxide lithium ion sieve, manganese oxide lithium ion sieve and titanium oxide lithium ion sieve, more preferably Li 1.33 Mn 1.67 O4, Li2TiO3 and Li4Mn5O 12 At least one of; Preferably, R1 is a propyl group and R2 is an -O-M3 group; Preferably, R1 is propyl and R2 is methyl; Preferably, R1 is ethyl-n-propylamino and R2 is methyl; Preferably, R1 is an ethyl-n-propylamino group, and R2 is an -O-M3 group.

3. A separation membrane, characterized in that: The separation membrane comprises a separation layer, wherein the separation layer comprises the polyamide material containing the lithium ion sieve according to claim 1 or 2.

4. The separation membrane according to claim 3, wherein The separation membrane comprises a bottom layer, a porous support layer and a separation layer in sequence; Preferably, the porosity of the bottom layer is 35-60%; Preferably, the thickness of the bottom layer is 30-150 μm, preferably 50-120 μm; Preferably, the thickness of the porous support layer is 10-100 μm, preferably 30-60 μm; Preferably, the average pore size of the porous support layer is 15-30 nm.

5. The separation membrane according to claim 4, wherein The material of the bottom layer is selected from polyester and / or polyethylene; And / or, the material of the porous support layer is selected from at least one of polyethersulfone, polysulfone, polyaromatic ether, polybenzimidazole, polyetherketone, polyetheretherketone, polyacrylonitrile, polyvinylidene fluoride and polyaryletherketone, and the weight average molecular weight of the material of the porous support layer is 50-150kDa.

6. The separation membrane according to claim 4, wherein The thickness of the separation layer is 80-110 nm; And / or, the average pore size of the separation layer is 0.2-0.3 nm.

7. A method for preparing a polyamide material containing a lithium ion sieve, characterized in that: The method comprises: using a dispersion containing polyamine and a solution containing polyacid chloride to form the polyamide material through interfacial polymerization; Wherein, the dispersion containing polyamine also contains aminosilane-modified lithium ion sieve.

8. The method according to claim 7, wherein: The interfacial polymerization is carried out on a substrate; Preferably, the interfacial polymerization method includes: contacting the surface of the substrate with a dispersion containing polyamine and a solution containing polyacyl chloride in sequence; Preferably, the polyamine is selected from at least one of polyethyleneimine, triethylenetetramine, tetraethylenepentamine, diethylenetriamine, polyethylenepolyamine, piperazine, m-phenylenediamine and p-phenylenediamine, preferably polyethyleneimine and / or piperazine; Preferably, the polyacyl chloride is selected from at least one of trimesoyl chloride, terephthaloyl chloride, isophthaloyl chloride and phthaloyl chloride, preferably trimesoyl chloride and / or terephthaloyl chloride.

9. The method according to claim 7 or 8, wherein: In the dispersion containing polyamine, the mass concentration of the polyamine is 0.1-3wt%, preferably 0.5-2.5wt%; Preferably, the aminosilane-modified lithium ion sieve has a structure as shown in formula (II), In formula (I), R1 is selected from H, C1-C6 alkyl and C1-C6 amine; R2 is selected from H, -O-M3 and C1-C6 alkyl, M1, M2 and M3 are each independently a lithium ion sieve; Preferably, the preparation method of the aminosilane-modified lithium ion sieve comprises: mixing the lithium ion sieve and aminosilane in a solution state, and performing a modification reaction under acidic conditions; Preferably, the mass ratio of lithium ion sieve to aminosilane is 1:(0.1-1.5); Preferably, the mass concentration of lithium ion sieve in the solution is 0.5-1.5 mg / ml; Preferably, the acidic condition is a pH of 1-3; Preferably, the modification reaction conditions also include: temperature of 70-90°C and time of 5-8h; Preferably, the preparation method of the aminosilane-modified lithium ion sieve further comprises: sequentially subjecting the material obtained by the modification reaction to centrifugation, first drying, ball milling and second drying.

10. The method according to claim 9, wherein: In the modification reaction, the lithium ion sieve is selected from at least one of aluminum hydrotalcite bimetallic oxide lithium ion sieve, manganese oxide lithium ion sieve and titanium oxide lithium ion sieve, more preferably Li 1.33 Mn 1.67 O4, Li2TiO3 and Li4Mn5O 12 At least one of; and / or, in the modification reaction, the average particle size of the lithium ion sieve is 10-200 nm; And / or, in the modification reaction, the aminosilane is selected from the structure shown in any one of formula (a) to formula (f); and / or, in the dispersion containing the polyamine, the mass concentration ratio of the aminosilane-modified lithium ion sieve to the polyamine is 1:(4-60); and / or, relative to 1m 2 The substrate is used in an amount of 5-500 mg of the aminosilane-modified lithium ion sieve.

11. The method according to claim 7, wherein: In the solution containing polyacid chloride, the concentration of polyacid chloride is 0.01-1 wt %, preferably 0.05-0.5 wt %.

12. The method according to claim 8, wherein: The substrate is in contact with the dispersion containing the polyamine for 5-100 seconds, preferably 10-60 seconds, and the contact temperature is 20-40° C., preferably 28-32° C.; and / or, the substrate is contacted with the solution containing polyacid chloride for 10-200 s, preferably 20-120 s, at a temperature of 20-40° C., preferably 28-32° C.; and / or, after contacting with the dispersion containing polyamine and the solution containing polyacid chloride, the method further comprises: heat treating the product after interfacial polymerization; Preferably, the heat treatment conditions include: a temperature of 40-150° C., preferably 50-120° C.; and a heat treatment time of 0.5-10 minutes, preferably 1-5 minutes.

13. A method for preparing a separation membrane, characterized in that: The method comprises the preparation method of the polyamide material containing lithium ion sieve according to any one of claims 7 to 12.

14. The method according to claim 13, wherein: The interfacial polymerization is carried out on a substrate comprising a porous support layer and a bottom layer; Preferably, the conditions of the interfacial polymerization further include making the thickness of the separation layer 80-110 nm; Preferably, the method further comprises the step of preparing a porous support layer on the bottom layer, the step comprising: coating a solution containing a porous support layer material on the bottom layer, and soaking the solution in water at 10-30° C. for 10-60 min to form a porous support layer on the surface of the bottom layer; the conditions for preparing the porous support layer preferably include making the thickness of the porous support layer 10-100 μm, preferably 30-60 μm; Preferably, in the solution containing the porous support layer material, the mass concentration of the porous support layer material is 10-20wt%; Preferably, the solvent in the solution containing the porous support layer material is at least one of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone and dimethyl sulfoxide; Preferably, the thickness of the bottom layer is 30-150 μm, preferably 50-120 μm; and / or, the material of the bottom layer is selected from polyester and / or polyethylene; and / or, the porosity of the bottom layer is 35-60%; And / or, the material of the porous support layer is selected from at least one of polyethersulfone, polysulfone, polyaromatic ether, polybenzimidazole, polyetherketone, polyetheretherketone, polyacrylonitrile, polyvinylidene fluoride and polyaryletherketone, and the weight average molecular weight of the material of the porous support layer is 50-150kDa.

15. A separation membrane prepared by the method according to any one of claims 13 to 14.

Citation Information

Patent Citations

  • Lithium-ion permselective membrane and preparation method thereof

    CN105903361A

  • Preparation method and application of modified hollow mesoporous silicon sphere adsorbent

    CN106902781A

  • Preparation method of porous spinning composite material and lithium extraction application thereof

    CN112619621A

  • Nanofiltration membrane for extracting lithium from salt lake as well as preparation method and application of nanofiltration membrane

    CN114177775A

  • Preparation method for porous spinning composite material, and application thereof in lithium extraction

    WO2022134221A1